Experimental Studies on the Performance of Graphene Oxide Based Hybrid Nanopolymers for Bearing Applications - Geetha Rajamani; Madhan Mohankumar; Gopinath Dhamodaran; S. Om Prakash; A. Johnson Santhosh (International Journal of Polymer Science)
In this experimental study, graphene oxide-blended glass-filled nylon (GO-GFN) hybrid nanopolymer composites were developed and characterized. Transmission electron microscopic studies were performed to study the dispersion of graphene oxide in glass-filled nylon composites. Dynamic mechanical analysis and thermogravimetric analyses were conducted on the fabricated hybrid nanopolymer composites to analyze the mechanical and thermal stability. Mechanical properties were investigated by tensile test. The test showed improvements in young’s modulus and tensile strength. Water absorption test was conducted to study the water absorption resistance of the hybrid nanopolymer composites. Finally, roller bearings with graphene oxide and glass-filled nylon were fabricated and analyzed for wear under varying load and speed conditions in the test rig developed in-house. The tests proved the suitability of deploying hybrid nanopolymer composites for bearing applications.